IDENTIFIKASI DAN UJI AKTIVITAS SENYAWA FLAVONOID DARI EKSTRAK DAUN TREMBESI (Samanea saman (Jacq.) Merr) SEBAGAI PENGENDALI JAMUR Fusarium sp. PADA TANAMAN BUAH NAGA - Sariningsih, Putu; Susanah Rita, Wiwik; Puspawati, Ni Made (Jurnal Kimia (Journal of Chemistry), 2015)
This study aimed to examine antifungal activity of Trembesi ( Samanea saman (Jacq.) Merr) leaves extract against Fusarium sp on dragon fruit and to identify types of flavonoid compounds present in the extracts. Isolation of the flavonoids was started by maceration followed by fractionation into n-hexane, chloroform, and ethyl acetate respectively. Separation was carried out by preparative layer chromatography while identification was done using Ultraviolet-Visible and Infrared spectrophotometer. Antifungal activity test showed that ethylacetate extract has mild activity in inhibiting the growth of Fusarium sp. (inhibition zone 6.75 mm).  The antifungal activity testing of three isolates positive flavanoid (B 4 , B 5 , B 6 ) showed at the concentration of 10 % they have not given activity yet. The infrared spectra of isolates (B 4 , B 5 , B 6 ) were very similar, therefore they have the same functional groups (OH, C-OH, aromatic CH, aliphatic CH, C=O, C-O-C ether, and aromatic C=C). The UV-Vis spectra showed isolates B 4 gave absorption at a wavelength of 336.00 nm (band I) and 268.40 nm (band II), isolates B5 at 269.20 nm (bands II), and 325.40 nm (band I), and isolates B 6 at 475.40 nm (bandI) and 282.40 nm (band II). Further UV-Vis identification using shift reagents suggested that isolates B 4 was tentatively identified as 3,7,8,4 ', 5' pentahydroxy flavonols, isolates B 5 as 3,5,4 'trihydroxy flavones, and  isolate B 6 as 3,5,7,8,3', 4 'hexahidroxy anthocyanine .
Keywords: Samanea saman (Jacq.) Merr, flavonoid, antifungal activity, Fusarium, sp